Diseño y construcción de un reactor piloto de pirólisis de neumáticos usados (2023)
The content of this project begins with the investigation of the problematic generated by the disposition of end-of-life tires and the background at legislative level in Bogota city. The composition of tires and their manufacturing process are investigated. An alternative to the linear economy model is proposed through the application of a process that contributes to transform this waste into value-added products, within the framework of application of the circular economy model. The fundamentals of the pyrolysis process are defined. The variables that most influence the process are studied, as well as the applications of by-products at an industrial and commercial level.